Kiprah Syaikh Muhammad Arsyad Thalib Lubis (1908-1972) dalam Bidang Politik - Samsul Bahri (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2024)
This research aims to find out the work of Syaikh Muhammad Arsyad Thalib Lubis (1908-1972), the founding figure of the Islamic mass organisation Al-Jam'iyatul Washliyah, in the political field. The research method consists of four stages, namely heuristic (source collection), verification (sorting / selection), interpretation (interpretation) and historiography (writing). The results of this study show that Syaikh Muhammad Arsyad Thalib Lubis is not only a preacher, teacher, writer, and leader of religious rituals, but also a scholar who is deeply involved in politics in the broader political sense. This political work has been going on for a very long time, from the colonial era until after independence. There were seven actions of Syaikh Muhammad Arshad Thalib Lubis in the political field, viz: (1) his support, through Al-Washliyah, for the existence of the Indonesian Islamic Assembly A'la, which was founded in 1937; (2) his support for Indonesian independence, which was proclaimed by Bung Karno in 1945; (3) his active defence of Indonesian independence through guerrilla warfare, (4) rejecting the formation of the East Sumatra State Federation (NST), (5) fighting for the establishment of Islam in Indonesia through the Constituent Assembly, (6) rejecting the communist ideology that developed in Indonesia, and (7) mediating conflicts between rebels in Indonesia and the central government